El Servicio Histórico del Colegio Oficial de Arquitectos de Madrid - Sanz Hernando, Alberto (arq.urb, 2013)
This paper presents the succinctly story of the Historical Service of the College of Architects of Madrid (COAM), since its founding in 1975 until today. This institution and its collections give the possibility of direct knowledge of the primary sources, ie, the original projects and graphics and textual documentation generated, supported by the secondary, literature, reports and photographic critics of the building, which are the basic actions involved in the investigation and analysis of architecture.